2004
DOI: 10.1590/s0074-02762004000700010
|View full text |Cite
|
Sign up to set email alerts
|

Trichurid nematodes in ring-necked pheasants from backyard flocks of the State of Rio de Janeiro, Brazil: frequency and pathology

Abstract: The present investigation is related to the frequency of infection and to the gross and microscopic lesions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
3
12
1
Order By: Relevance
“…The prevalence and the intensity of infection reported here for E. annulatus were low, similar to those reported for pheasants by Pinto et al (2004) in Brazil and by Tampieri et al (2005) in Europe. Although gross and microscopic alterations induced either by E. annulatus or B. obsignata were not described in studies of the former authors, there is the description of lesions caused by E. perforans in pheasants that are similar to those provoked by E. annulatus presently observed in turkeys and that consist of a mild esophagitis and epithelium elongated-lined (tunnels) of the crop lined with eosinophilic material, in the presence of cellular debris and eggs of the parasites.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The prevalence and the intensity of infection reported here for E. annulatus were low, similar to those reported for pheasants by Pinto et al (2004) in Brazil and by Tampieri et al (2005) in Europe. Although gross and microscopic alterations induced either by E. annulatus or B. obsignata were not described in studies of the former authors, there is the description of lesions caused by E. perforans in pheasants that are similar to those provoked by E. annulatus presently observed in turkeys and that consist of a mild esophagitis and epithelium elongated-lined (tunnels) of the crop lined with eosinophilic material, in the presence of cellular debris and eggs of the parasites.…”
Section: Discussionsupporting
confidence: 91%
“…These alterations, apparently had no effect for the feeding process of the birds, and the absence of clinical signs associated to the parasitism with E. annulatus observed here, are probably related to the low parasite burden (5 nematode specimens) harbored by the single infected turkey, what is in accordance with Pinto et al (2004), since this nematode is known to be highly pathogenic to turkeys. According to Hurst et al (1979) that reported to the death of 23 young (6-10 weeks) turkeys out of the 56 observed and infected with E. anullatus; the infection was the cause of inappetence, loss of weight and lethargy.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Enteric Capillariasis caused by B. obsignata is known to occur in all birds belonging to Anseriformes, Ciconiiformes, Columbiformes, Galliformes, Piciformes and Psittaciformes (Jortner et al 1967;Rickard & Pohl 1969;Pinto et al 2004;Pinto et al 2008;Yabsley 2008;Park & Shin 2010;D' Avila et al 2011). There are few reports traced on enteric Capillariasis caused by B. obsignata infections in turkeys, and the severity of the disease was different in each report (Hurst et al 1979;De Rosa & Shivaprasad 1999;Pinto et al 2008).…”
Section: Discussionmentioning
confidence: 99%